Board independence, family control, and performance in Taiwanese listed semiconductor companies - Kweh Q.L.; Kuo K.-C.; Wang W.-K.; Liu H.-M. (Hitotsubashi University, 2023)
We examine the relationship between board independence, family control, and operating efficiency, and the moderating effect of family control on the relationship between board independence and operating efficiency. We apply the dynamic slacks-based measure (DSBM) model to estimate operating efficiency. Usinga sample of 42 Taiwanese listed semiconductor companies for the period 2005-2012, we employ truncated regression with a bootstrapping procedure for multivariate analysis. The presence of board independence is significantly positively related to operating efficiency. Family control has a negative impact on operating efficiency. The positive effect of board independence on operating efficiency is significantly weakened in family companies. 2015 Hitotsubashi University.